The improvement of predictability in Clear Aligner treatment in conjunction with Digital Monitoring - Sara Caruso; Silvia Caruso; Mariaelena De Felice; Roberto Gatto; Vincenzo D'Antò (Publymed, 2023)
The primary objective of this study is to evaluate the Tpredictability of orthodontic treatment with clear aligners monitored by Dental Monitoring® (DM) and to assess if using the DM system can actually lead to better results and shorter treatment times. A secondary objective is to assess whether the DM system can be more effective in monitoring one type of malocclusion over another, namely: crowding, crossbite and diastema. A total of 55 patients treated consecutively with clear aligners were selected. All patients were asked to use the DM system with scheduled appointments at 7-8-week intervals. Our results show that photos and scans taken in the chair correspond accurately to the photos and scan taken by the patient using the DM system. Results also show that the different malocclusions did not show any difference in predictability when using the DM system. This study concluded that treatment time was indeed reduced in terms of total number of in-office appointments.